Hubungan Pengetahuan, Sikap dan Perilaku Ibu Rumah Tangga Dengan Kejadian Demam Berdarah Dengue di Kelurahan Melayu Kota Bima Tahun 2024 - Fatihah, Raisah Amani; Andriana, Ana; Sukmajaya, Ali; Rinayu, Nisia Putri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
Dengue Hemorrhagic Fever is an endemic disease that can become an extraordinary event due to the bite of Aedes aegypti and Aedes albopictus mosquitoes, especially in tropical and subtropical areas. This study aims to analyze the relationship between knowledge, attitudes, and behavior of housewives regarding DHF prevention in Melayu Village, Bima City, in 2024. The study used an analytical design with a cross-sectional approach, involving 90 respondents selected by purposive sampling. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed that housewives' knowledge had a significant relationship with dengue fever (p = 0.535), mothers' attitudes had a significant relationship with dengue fever (p = 0.000), and mothers' behavior also had a significant relationship with dengue fever (p = 0.000). Respondents with good knowledge, positive attitudes, and good behavior had a lower risk of developing dengue fever compared to respondents with poor knowledge, attitudes, and behavior. In conclusion, the knowledge, attitudes, and behavior of housewives play an important role in preventing dengue fever. Therefore, health education interventions need to be improved to reduce the incidence of dengue fever in the area.